On the nonperiodic groups, whose subgroups of infinite special rank are transitively normal - Kurdachenko, L.A.; Subbotin, I.Ya.; Velychko, T.V. (Доповіді НАН України, 2020)
This paper devoted to the nonperiodic locally generalized radical groups, whose subgroups of infinite special rank are transitively normal. We proved that if such a group G includes an ascendant locally nilpotent subgroup of infinite special rank, then G is Abelian. Досліджено неперіодичні локально узагальнені радикальні групи, в яких підгрупи нескінченного спеціального рангу є транзитивно нормальними. Доведено, що якщо така група G містить у собі висхідну локально нільпотентну підгрупу нескінченного спеціального рангу, то G абелева. Исследованы непериодические локально обобщенные радикальные группы, у которых подгруппы бесконечного специального ранга транзитивно нормальны. Доказано, что если в такую группу G входит восходящая локально нильпотентная подгруппа бесконечного специального ранга, то G абелева.